HOW TO INCREASE WORKFLOW EFFICIENCY FOR MICRO AND SMALL BUSINESSES WITH A CUSTOM-BUILT MOBILE APP IN HUNGARY - A CASE STUDY FOR A LANGUAGE LEARNING SCHOOL - Péntek, Ádám; Pierog, Anita; Kovács, Tamás (Applied Studies in Agribusiness and Commerce, 2024)
The increasing availability of information and communication technology (ICT) has boosted interest in ICT-based microservices. Limited research examines the efficacy of ICT-based microservices and administrative burden-alleviating solutions for small and medium enterprises (SMEs) within a domestic context. This study investigated the potential of such solutions through a case study on a custom language training SME. Key workflows with administrative burdens were identified using an expert interview, leading to the design and development of a custom mobile application. The researchers developed an easily adaptable, general-purpose layer structure during the development process. Results suggest automating essential, low-cost elements of SMEs' internal and external processes through digitalisation and on-demand support can increase competitiveness and employee satisfaction. Further research with a larger sample size could solidify these initial findings and inform broader SME development strategies. Additionally, investigating the long-term impact on factors like employee skill development and customer satisfaction would provide valuable insights for SMEs considering such solutions.